2006
DOI: 10.1177/000313480607201003
|View full text |Cite
|
Sign up to set email alerts
|

Gallbladder Management during Laparoscopic Roux-en-Y Gastric Bypass Surgery: Routine Preoperative Screening for Gallstones and Postoperative Prophylactic Medical Treatment are Not Necessary

Abstract: In the bariatric surgery literature, the optimum approach to the gallbladder is controversial. Recommendations range from concomitant cholecystectomy to selective screening and postoperative medical prophylaxis. At our institution, we have taken a highly selective approach where patients are not routinely screened for gallstones, nor are they medically treated postoperatively with bile salts. We have reviewed our experience with this approach. From January 2003 to January 2005, 407 laparoscopic Roux en Y gastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(12 citation statements)
references
References 13 publications
0
11
1
Order By: Relevance
“…RYGB and VSG led to a steep rise in AP rates in the first 6 months after surgery, ranging between 0.17% and 0.21%, but not after HR. These rates are slightly lower than the previously reported range of 0.2–1.04%, probably because of different designs, small sample sizes, and variable follow up in prior studies 22 , 23 , 25 , 26 , 28 – 33 . VSG led to a higher pre- to post-surgery AP risk when compared to RYGB and HR after adjusting for multiple covariates.…”
Section: Discussioncontrasting
confidence: 67%
“…RYGB and VSG led to a steep rise in AP rates in the first 6 months after surgery, ranging between 0.17% and 0.21%, but not after HR. These rates are slightly lower than the previously reported range of 0.2–1.04%, probably because of different designs, small sample sizes, and variable follow up in prior studies 22 , 23 , 25 , 26 , 28 – 33 . VSG led to a higher pre- to post-surgery AP risk when compared to RYGB and HR after adjusting for multiple covariates.…”
Section: Discussioncontrasting
confidence: 67%
“…Based on such estimates, concurrent prophylactic cholecystectomy during RYGB has previously been recommended, based on the rationale that the conversion rate to open surgery is not increased, neither is operative time nor hospital stay [173]. Further studies, however, have suggested that most patients remain asymptomatic [156,157,160,168,169,[174][175][176][177][178] and never require further interventions following RYGB. Thus, concurrent (prophylactic) cholecystectomy during laparoscopic bypass surgery is no longer routinely performed [168,169,[174][175][176]179].…”
Section: Should Prophylactic Cholecystectomy Be Performed During Barimentioning
confidence: 99%
“…The rate of weight loss is also considered an independent prognostic factor in gallstone formation [33] and is suggested to be directly correlated with cholecystectomy frequency [31]. Prophylactic cholecystectomy, during bariatric surgery, is not considered beneficial nowadays because it is associated with higher early complications rate [34,35], longer length of hospitalization [35], and longer operative time [36,37]. In a prospective study with 1398 patients who received bariatric surgery, only 7.8% of patients developed symptomatic gallbladder disease within 4 years [31].…”
Section: Discussionmentioning
confidence: 99%